PENULISAN DAN PENERBITAN BUKU AJAR: MINAT DAN RESPONS GURU - Achmad Dhany Fachrudin; Intan Bigita Kusumawati; Siti Nuriyatin; Eka Nurmala Sari Agustina; Soffil Widadah; Endang Wahju Andjariani (JURNAL PADI (Pengabdian mAsyarakat Dosen Indonesia), 2022)
Books are very important in the world of education, it is hoped that teachers are also able to write their own books. This community service aims to improve teachers' ability to write books and also to find out teachers' interests and responses during seminars. This activity took place at the Integrated Islamic Education Institute Insan Kamil Sidoarjo which was attended by elementary and junior high school teachers at the Institute. This Community Service is divided into three activities, namely: (1) Pre-Activity, (2) Implementation, and (3) Post-Activity. After delivering the material, a questionnaire was also given to the participants related to the material, interests, and confidence in writing and publishing books. Overall the seminar participants gave a positive response to the seminar activities. Of the 13 statements given, only two statements did not get a 100%. After the seminar was given, there were still participants who had difficulty managing book publication. There are also seminar participants who still don't feel the benefits of writing books to be able to become additional income for teachers